Case reportA very rare case of coexistence of ventricular noncompaction cardiomyopathy, myocardial bridging and atherosclerosis - Erdogan, Ercan; Akkaya, Mehmet; Bacaksiz, Ahmet; Tasal, Abdurrahman; Sevgili, Emrah (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Noncompaction of the ventricular myocardium is a rare congenital heart disease, presumably caused by the intrauterine arrest of the myocardial compaction process at the beginning of fetal development. It could remain asymptomatic or manifest with congestive heart failure, arrhythmias, and systemic thromboemboli. Here we report a 55-year-old man who was admitted to hospital with chest pain and dyspnea, whose further evaluation revealed left ventricular noncompaction cardiomyopathy accompanying myocardial bridging and stenosis of the right coronary artery.